Penerapan Critical Path Method pada Penyelesaian Proyek Rehabilitasi Jalan Parigi Lama di Kabupaten Sumedang - Ilyas Habibi; Farhan Zaidan Nugraha; Sutrisno Sutrisno (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2023)
Project management is an effort to organize a project plan by taking into account the time and availability of resources. One of the projects used as the source of this research is the road rehabilitation project in Sumedang district. Roads are infrastructure supporting access to transportation and as a determinant of progress and economic development of a region. Sumedang City is a developing city and requires better quality and quantity of transportation. Many alternative roads are damaged and require road widening, one of which is Parigi Lama road. To improve and widen roads, the local village government undertakes a road rehabilitation project. This project is planned to be completed within 60 days. The road rehabilitation project is expected to run smoothly and be completed faster than the estimated time that has been planned. In this study the author uses the critical path method (CPM) to get the optimal time. From the results of calculations using the critical path method (CPM) this Parigi Lama road rehabilitation project can be completed within 42 days